2018
DOI: 10.1111/nph.15386
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of alternative explanations for widespread cytonuclear discordance in annual sunflowers (Helianthus)

Abstract: Cytonuclear discordance is commonly observed in phylogenetic studies, yet few studies have tested whether these patterns reflect incomplete lineage sorting or organellar introgression. Here, we used whole-chloroplast sequence data in combination with over 1000 nuclear single-nucleotide polymorphisms to clarify the extent of cytonuclear discordance in wild annual sunflowers (Helianthus), and to test alternative explanations for such discordance. Our phylogenetic analyses indicate that cytonuclear discordance is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
107
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(119 citation statements)
references
References 91 publications
9
107
2
1
Order By: Relevance
“…In this study, the chloroplast phylogeny did not recover any perennial Helianthus species as reciprocally monophyletic. This is in line with previous findings in other perennial Helianthus [21] as well as in annual Helianthus taxa [52]. These results can be explained by incomplete lineage sorting (ILS) or by reticulation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, the chloroplast phylogeny did not recover any perennial Helianthus species as reciprocally monophyletic. This is in line with previous findings in other perennial Helianthus [21] as well as in annual Helianthus taxa [52]. These results can be explained by incomplete lineage sorting (ILS) or by reticulation.…”
Section: Discussionsupporting
confidence: 93%
“…These associations reflect historical organelle capture events occurring among pairs of taxa that are interfertile [56]. Previous results in annual Helianthus [52] have indicated that, relative to ILS, reticulation is likely more important in generating patterns of cytonuclear discordance such as those observed here. Indeed, we identified several cases of haplotype sharing among geographically proximate populations (Figure 2), which would indicate that hybridization is more likely than ILS.…”
Section: Discussionsupporting
confidence: 73%
“…Potential cytoplasmic introgression driven by selection among Helianthus species was also reported, leading to widespread CN discordance in genealogies [77]. Selection might shape the pattern of organellar variation for some specific genes, resulting in adaptive introgression of the plastid genomes favoring local adaptation [77]. Cytoplasmic genomes can be important capacitors for the generation of novel phenotypes in specific environments, as shown in a study on Arabidopsis thaliana [42].…”
Section: Cytonuclear Coevolution and Environmentmentioning
confidence: 92%
“…They revealed that the cytoplasms of these species were adapted to each specific habitat, suggesting that variation in the organellar genome could contribute to local adaptation and ecological differentiation [76]. Potential cytoplasmic introgression driven by selection among Helianthus species was also reported, leading to widespread CN discordance in genealogies [77]. Selection might shape the pattern of organellar variation for some specific genes, resulting in adaptive introgression of the plastid genomes favoring local adaptation [77].…”
Section: Cytonuclear Coevolution and Environmentmentioning
confidence: 99%
“…The call set included the 1518 samples described above, the Sunflower Association Mapping (SAM) population (a set of cultivated H. annuus lines 54 ), and wild Helianthus samples previously sequenced for other projects [54][55][56] , for a total of 2392 samples (Supplementary Table 1). The additional samples were included to improve SNP calling, and to identify haploblock genotypes.…”
Section: Variant Callingmentioning
confidence: 99%